NEONATAL CARE RESOURCES AND SERVICES BY NURSES IN SELECTED TERTIARY HEALTH INSTITUTIONS IN SOUTH EASTERN NIGERIA - , Chiejina Edith Nkechi; Agu Earnest Emeka,; Ndie Elkenah Chibuike, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Neonatal developmental stage is a critical period, and therefore requires adequate uncompromised equipment as well as competent professionals in the care of the newborn. This study focused on neonatal care resources, and services by nurses in tertiary health institutions in South Eastern Nigeria. It was a descriptive cross-sectional research design, Multistage sampling technique was used in selecting 440 respondents. Two research questions and two null hypotheses guided the study. Questionnaires on neonatal care services by nurses in Tertiary health Institutions and checklist on assessment of available and functional equipment, drugs and nursing staff strength in tertiary health institutions were the instruments used for data collection in the study. Standard descriptive statistics of frequency distribution , means and standard deviation (SD) were used to summarize the variables. Mean scores and percentages were used to answer the research questions while Mann-Whitney U and Kruskal Wallis tests were adopted in testing the null hypotheses at 0.05 level of significance. The results revealed availability of essential equipment for neonatal care in the tertiary health institutions as recommended by WHO, and gender of nurses had no significant influence on the quality of neonatal care given by nurses (ⱬ score = 0.40; p-value = 0.69). In addition, years of working experience of nurses was found to have significance influence on the quality of neonatal care given by nurses (x2 =25.63; p-value = 0.00).